1998
DOI: 10.1111/j.1468-3083.1998.tb00925.x
|View full text |Cite
|
Sign up to set email alerts
|

Generalized pustular drug eruptions: confirmation by in vitro tests

Abstract: The diagnosis of pustular drug eruptions depends on circumstantial evidence, some characteristic clinicopathological findings and exclusion of alternative diagnoses of other disseminated pustular eruptions. In vitro tests, namely MIF and MCD tests, are a useful diagnostic aid in the identification of the offending drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…In vitro assays based on drug‐related T‐cell activity have been used previously in the evaluation of various types of CDRs. In vitro release of MIF, a correlate of DTH and cell‐mediated immunity (CMI), 9,30 has been reported recently as a diagnostic tool in controlled studies of various types of adverse CDRs, 10−16,23 including TEN. 15 The use of the lymphocyte transformation test in TEN is controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro assays based on drug‐related T‐cell activity have been used previously in the evaluation of various types of CDRs. In vitro release of MIF, a correlate of DTH and cell‐mediated immunity (CMI), 9,30 has been reported recently as a diagnostic tool in controlled studies of various types of adverse CDRs, 10−16,23 including TEN. 15 The use of the lymphocyte transformation test in TEN is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Drug‐related T‐cell activity in CDRs may be assessed using in vitro tests, such as the lymphocyte transformation test, or lymphokine release tests, 7−9 such as the macrophage migration inhibition factor (MIF) test 10−16 and the leukocyte inhibitory factor (LIF) test. 17−22 The diagnostic role of these nonstandardized in vitro tests is still controversial.…”
mentioning
confidence: 99%
“…The mast cell degranulation test [41,42], macrophage migration inhibition factor test, interferon-γ release test [43] and lymphocyte proliferation responses [44] have been published. For the latter, it could be demonstrated that it correlated with patch tests in 2 patients [45].…”
Section: Treatmentmentioning
confidence: 99%
“…The risk of AGEP with patch testing is considered to be low but not negligible [245]. A small number of studies have supported a role for LTT [246], IFN-γ release [247], lymphokine macrophage migration inhibition factor release assays [241] but these in vitro tests are not widely available and its value remains to be determined in large cohorts. …”
Section: Diagnostic Testsmentioning
confidence: 99%
“…The pathogenesis of AGEP has been elucidated by patch [239], [240] and in vitro tests [241]- [243] and initially involves activation, expansion and subsequent migration of drug-specific CD4 and CD8 cells to the skin. The initial influx of CD8 cytotoxic T cells results in apoptosis of keratinocytes and the formation of subcorneal vesicles.…”
Section: Pathogenesismentioning
confidence: 99%